Understanding Today's Mobile Users' Expectations of Tomorrow's Mobile Services - Högg, Roman; Martignoni, Robert; Stanoevska-Slabeva, Katarina (My University, 2007)
This paper introduces the results of two independently conducted surveys, both looking at the expectations of today's users of future mobile broadcasting / multicasting services. The goal is to explain what today's mobile users think about and expect from new mobile services and technologies.